Soil erosion evaluation by using musle in regards of erosion sediment control practices for construction site / Siti Isma Hani Ismail and Hooi Min Yee - Ismail, Siti Isma Hani; Hooi, Min Yee (2012)
Throughout construction projects, large areas of soil are exposed to the risk of water erosion due to extensive earthworks activities. Such projects pose a significant risk to the environment, which must be addressed by developers and contractors wisely. Bare slopes and drains choked with sediment can often result in a significant increase in sediment loads to receiving waters while the construction techniques used on site can cause offsite contamination. Erosion from the study area occurred from removal of vegetation covers, high rainfall intensity and the failure of the sediment basins to function effectively. The present study aims to evaluate erosion and sediment yield due to stormwater flows on a construction site located at Sungai Ara, Penang State of Malaysia. The soil loss on site was evaluated by using empirical erosion modelling namely Modified Universal Soil Loss Equation (MUSLE) by Onstad and Foster (1975). Hydraulic structure known as Sharp Crested Rectangular Weir were built on site for this measurement. Results shown that large amount of sediment has being eroded from the study area. The highest erosion rates estimated is 64 tons/ha during the storm event.